Management Relations with Organized Public Employees — Theory, Policies, Programs - Cardin, Jean-Réal (Relations industrielles / Industrial Relations, 1963)
The article reviews the book, "Management Relations with Organized Public Employees — Theory, Policies, Programs," edited by Kenneth O. Warner.